2004
DOI: 10.1063/1.1763639
|View full text |Cite
|
Sign up to set email alerts
|

Hard metallic glass of tungsten-based alloy

Abstract: A tungsten-based ductile metallic glass with the composition W46Ru37B17 was produced by a single-roller melt-spinning procedure. The differential scanning calorimetry measurement showed a two-step crystallization with the first crystallization temperature as high as 1174 K. Young’s modulus of the glass at room temperature was estimated to be 309±20 GPa by a nanoindentation test and the Vickers hardness at room temperature was 16.8±1 GPa. These values are higher than those of any metallic glasses so far reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 4 publications
3
27
1
Order By: Relevance
“…This is somehow unexpected because for BMGs there exists a universal correlation between the Yough's modulus and the Vicker's hardness as documented in Refs. [19,93,94].…”
Section: Discussion and Remarksmentioning
confidence: 99%
“…This is somehow unexpected because for BMGs there exists a universal correlation between the Yough's modulus and the Vicker's hardness as documented in Refs. [19,93,94].…”
Section: Discussion and Remarksmentioning
confidence: 99%
“…Some bulk metallic glasses ͑BMGs͒ and amorphous ribbons exhibit outstanding mechanical properties, [1][2][3][4][5] and good corrosion and wear resistance. 6 This makes them attractive as structural materials.…”
mentioning
confidence: 99%
“…For example, the BMGs based on Pr or Ce elements (with low E) have the lowest values of E among existing BMGs; while the Co-and Fe-based BMGs (for pure Co and Fe, E is larger than 200 GPa) all have high values of E and strength [15]. In fact, tungsten-based glasses [16] (For W, EZ411 GPa) have an extreme high E (Z309 GPa) and exceptionally stronger mechanical properties than any existing metallic glass. Previous work also indicated that the elastic constants of BMGs show a good correlation with the weighted average of the elastic constants of the constituent elements, i.e.…”
Section: Glassy Alloysmentioning
confidence: 96%
“…The studies are mostly focused on soft magnetic properties because of their low GFA and small sample sizes. Recently, Fe 75KxKy Cr x Mo y C 15 B 10 [5] and Fe 43 Cr 16 Mo 16 (C, B, P) 25 [6] which exhibit high corrosion resistance and high GFA were developed. These Fe-based BMGs also are called nonmagnetic bulk amorphous alloys due to the absence of magnetic properties at room or higher temperature.…”
Section: Introductionmentioning
confidence: 99%